Outcome after neoadjuvant chemotherapy in estrogen receptor-positive and progesterone receptor-negative breast cancer patients: a pooled analysis of individual patient data from ten prospectively randomized controlled neoadjuvant trials - Van Mackelenbergh, Marion T.; Denkert, Carsten; Nekljudova, Valentina; Karn, Thomas; Schem, Christian; Marme, Frederik; Stickeler, Elmar; Jackisch, Christian; Hanusch, Claus; Huober, Jens; Fasching, Peter; Blohmer, Jens-Uwe; et al. (Breast Cancer Research and Treatment, 2018)
The estrogen receptor (ER) is involved in control of progesterone receptor (PgR) expression and lack of PgR may be also a surrogate of altered growth factor signaling. The aim of this study was therefore to investigate PgR expression as predictive factor for response to neoadjuvant therapy and long-term outcome.Five thousand and six hundred and thirteen patients with primary breast cancer and positive ER expression from ten German neoadjuvant trials of anthracycline and taxane-based chemotherapy were included. Pathologic complete response (pCR), disease-free survival (DFS), distant disease-free survival (DDFS), overall survival (OS), and local recurrence-free survival (LRFS) were compared according to PgR expression.The lack of PgR expression (1172 patients) was associated with grade 3 (38.4 vs. 26.3%; p < 0.001), nodal involvement (>cN2) (6.8% vs. 4.7%; p = 0.004), and HER2 positivity (36.2 vs. 22.3%; p < 0.001). pCR rates of PgR-negative tumors were higher in the entire cohort (13.8 vs. 7.5%; p < 0.001) and in the HER2-negative subgroup (11.2 vs. 5.8%; p < 0.001). In multivariable logistic regression, PgR negativity was an independent predictive factor for pCR overall (OR 1.76; p < 0.001) and in the HER2-negative patients (OR 1.99; p < 0.001). Patients with PgR-negative disease had significantly worse outcome (p < 0.001, respectively). Multivariable Cox regression analysis revealed that PgR was an independent prognostic factor for DFS, OS, DDFS, and LRFS.ER-positive/PgR-negative breast carcinomas are associated with higher response but also worse long-term outcome after neoadjuvant therapy. PgR negativity is an independent predictive factor for pCR after neoadjuvant chemotherapy in ER-positive HER2-negative breast cancer.
EVALuna2:56119